AKSELERASI PEMBANGUNAN E-GOVERNMENT DI DAERAH: ANALISIS PRAKTIK BAIK PEMERINTAH KABUPATEN SUMEDANG - Asep Cahyana (STISIP Widyapuri Mandiri, 2023)
ICT is a challenge and opportunity for local governments in effort to realize excellent service for the people. This paper aims to analize e-government efforts and achievements of the Sumedang District Government, as well as analyze the specific factors that have driven a leap in e-government development in the region. The author uses data obtained through online observation of the official website www.sumedang.go.id, digital application trials, as well as regulations, policy documents, journals, reports, online sources and other relevant documents. The author concludes that Sumedang Regency e-government development has passed the interactive phase towards the transactional phase. The author concludes that Sumedang Regency e-government development has passed the interactive phase towards the transactional phase. The acceleration of e-government by the Government of Sumedang Regency is determined by several factors, namely the political commitment of regional leaders that underlies policies, e-government strategies, programs and activities, development of human resources for apparatus, and multi-stakeholder collaboration.